Religion and intercultural communication competence - Nadeem, Muhammad Umar; Mohammed, Rosli; Dalib, Syarizan (IISTE, 2017)
The rush of international students has been increasing day by day in Malaysia. Religion is not a personal affair there and the foreigners are treated based on their religion. Several studies suggest to address religion in this regard. The aim of this study is to examine whether religion is having association with the intercultural communication competence (ICC) in Malaysian context. Literature has explored that religiosity has not been given attention by the researchers in the previous studies regarding the contributors of ICC. Although, religion is one of the crucial element behind every intercultural communication. Scholarships regarding the religiosity in terms of ICC would be fruitful for documenting the current situation of international students in Malaysia.